Price and Volume Divergence in China’s Real Estate Markets: The Role of Local Governments - Chang, Jeffery (Jinfan); Wang, Yuheng; Xiong, Wei (Review of Financial Studies, 2026)
Abstract During the COVID-19 pandemic (2020-2022), Chinese cities witnessed a paradox: residential land and new house prices surged while transaction volumes plummeted. We attribute this to local governments’ active price management through supply controls, land acquisitions by local government financing vehicles (LGFVs), and limits on new home sales permits. Cities more dependent on land sales and land-backed debt before the pandemic experienced greater price increases and price–volume divergence, with LGFVs buying more land at higher prices than other buyers. These interventions helped sustain fiscal financing but deepened developers’ financial distress, revealing unintended consequences of local governments’ fiscal strategies during downturns.